Molecular Epidemiology and Antimicrobial Resistance of Haemophilus influenzae in Adult Patients in Shanghai, China - Li, Xin-Xin; Xiao, Shu-Zhen; Gu, Fei-Fei; He, Wei-Ping; Ni, Yu-Xing; Han, Li-Zhong (Frontiers in Public Health, 2020)
Background: The serotype and antimicrobial resistance of Haemophilus influenzae in adult patients have changed due to the application of antimicrobials and H. influenzae type b (Hib) vaccine worldwide. However, the epidemiologic characteristics of H. influenzae in Shanghai are still unavailable. Objective: To determine the serotype distribution, antimicrobial resistance and multilocus sequence type (MLST) of H. influenzae in adult patients in Shanghai. Methods: A total of 51 clinical isolates from adult patients were consecutively collected. Serotypes were determined according to specific capsule gene, bexA, amplified by PCR. Antimicrobial susceptibility test was carried out by the broth microdilution method. β-lactamase production was detected by cefinase disk and the ftsI gene were amplified and sequenced to determine the penicillin binding protein 3 (PBP3) mutation. Molecular epidemiology was performed by MLST analyses. Results: All isolates studied were nontypeable H. influenzae (NTHi) and three of them (5.88%) caused invasive infection. The resistant rates of ampicillin and trimethoprim/sulfamethoxazole were both 45.10%. One third of these isolates produced TEM-1 type β-lactamase and 11.76% were β-lactamase negative ampicillin resistant strains (BLNAR). The PBP3 mutation was detected in 74.51% of the isolates, of which 12 belonged to group III. A total of 36 sequence types (STs) were identified among all isolates. Four isolates of ST103 (7.84%) all produced β-lactamase without mutation of PBP3. Conclusion:H. influenzae infections among adults in Shanghai are predominately caused by NTHi with genetic diversity among adult patients. The prevalence of both β-lactamase production and PBP3 mutation may contribute to high ampicillin resistance rate in Shanghai.